Case study on the feasibility of outsourcing within company X logistics limited. - Chan, Lee Yong. (2008)
The purpose of our project is carry out a stock take of the existing outsourcing efforts in Company X by conducting in-depth interviews with its departmental heads and subsequently recommend some measures to spur this effort.